PENGEMBANGAN ORGANISASI DAN BUDAYA ORGANISASI DALAM MENINGKATKAN EFEKTIVITAS ORGANISASI - Ani Sahadatina Sahadatina; Reza Dwi Rahmah; Machdum Bachtiar (Universitas Jabal Ghafur, 2026)
This study aims to analyze in depth the concept of organizational development and organizational culture in improving organizational effectiveness. The method used in this study is a literature review by examining various relevant scientific sources, such as national and international journals, reference books, and academic articles discussing organizational development, human resource development, organizational commitment, leadership, and organizational culture. This approach is conducted to obtain a comprehensive understanding of the factors influencing the success of organizational development in various contexts. The results of the study indicate that organizational development is a planned, systematic, and continuous change process aimed at improving organizational effectiveness through the improvement of structure, work systems, strategies, and individual behavior within the organization. Organizational development does not only focus on technical aspects but also includes behavioral and cultural aspects that serve as the foundation for the change process. In addition, the success of organizational development is strongly influenced by the strengthening of human resource competencies, high levels of organizational commitment, and leadership styles that encourage participation and innovation. Organizational culture plays a strategic role as a system of values, norms, and beliefs that shape the work behavior of organizational members. An adaptive culture that is open to change and oriented toward learning will foster an innovative and collaborative work environment. Conversely, a rigid culture can hinder the process of organizational transformation. Therefore, the integration between organizational development and the establishment of an adaptive organizational culture becomes a key factor in enhancing organizational effectiveness.